Islamic Peace Education: Internalization of God’s Feminine Names to Santri in the Syukrillah Islamic Boarding School - R. Widya Setiabudi Sumadinata; Otong Sulaeman; Dina Yulianti (State Institute of Islamic Studies (IAIN) Salatiga, 2020)
Amid public concern about increasing radicalism and intolerance among Indonesianstudents, discussions on the importance of peaceful education came again to draw attention. Through a qualitative research, we found a method of peaceful education teaching that is intrinsic and based on local wisdom about the feminine attributes of God which can be internalized by students so that they have a culture of peace. Through this method, the Syukrillah Islamic Boarding School, Cipongkor, West Java, has taught a comprehensive understanding of religion, recognition of different opinions on religions, and feminine characteristics which are essential qualities desired in peaceful education. This article offers a new perspective of peaceful education by adopting a local wisdom concept that hopefully enriches the discussion of peaceful education.